THE EFFECT OF TRAINING, MOTIVATION AND KNOWLEDGE OF ENTREPRENEURSHIP ON THE PERFORMANCE OF BROWN MEDIUM ENTERPRISES IN PACKAGING IN MAKASSAR CITY - Hasanuddin Djumakking (Journal of Social Sustainability Management, 2021)
This research is based on seeing the condition of Micro, Small and Medium Enterprises (MSMEs) in the city of Makassar which is less advanced than other areas in Indonesia. The knowledge of UKM players about the importance of Entrepreneurship Training, Motivation and Knowledge needs to be improved considering that Small Businesses are the backbone of a country's economy. The research aims to determine and analyze: 1) the effect of training, motivation, and entrepreneurial knowledge individually (partially) on the performance of small and medium-sized chocolate packaging entrepreneurs in Makassar City, 2) the effect of training, motivation, and entrepreneurial knowledge together ( simultaneously) on the performance of packaged chocolate small and medium entrepreneurs in Makassar City, and 3) the most dominant variable influencing the performance of packaged chocolate small and medium entrepreneurs in Makassar City. This research approach uses survey research that takes a sample from one population and uses a questionnaire as the main data collection tool. The research was carried out on packaged chocolate SMEs in Makassar City. When the research was conducted from December 2015 to February 2016. The population used in this study were all chocolate packaged SME entrepreneurs in Makassar City totaling 20 people. The sample selection in this study was carried out using a saturated sampling method (census), in which all populations were sampled, as many as 20 SME entrepreneurs of chocolate packaging in Makassar City. Quantitative data analysis techniques obtained from the results of the questionnaire using multiple regression analysis. The results of this study indicate that the strategy of developing Small and Medium Enterprises of the Cooperatives and SME Service of Makassar City is quite good when viewed from 3 strategic aspects, namely cost leadership (low costs including production costs, tools and raw materials), differentiation (creating different and unique products) , and focus (target buyers, product segments and marketing locations). This can be seen from the influence of training, the emergence of strong motivation and an increase in entrepreneurial knowledge on the performance of small and medium-sized chocolate packaging entrepreneurs in Makassar City. Penelitian ini di latarbelakangi melihat kondisi Usaha Mikro Kecil dan Menengah (UMKM) di kota Makassar yang kurang maju di banding daerah-daerah lain yang ada di Indonesia. Pengetahuan para pelaku UKM tentang pentingnya Pelatihan, Motivasi dan Pengetahuan Kewirausahaan perlu di tingkatkan mengingat Usaha Kecil adalah tulang punggung perekonomian sebuah negara. Penelitian bertujuan untuk mengetahui dan menganalisis : 1) pengaruh pelatihan, motivasi, dan pengetahuan kewirausahaan secara sendiri-sendiri (parsial) terhadap kinerja pengusaha kecil menengah coklat kemasan di Kota Makassar,2) pengaruh pelatihan, motivasi, dan pengetahuan kewirausahaan secara bersama-sama (simultan) terhadap kinerja pengusaha kecil menengah coklat kemasan di Kota Makassar, dan 3) variabel yang paling dominan berpengaruh terhadap kinerja pengusaha kecil menengah coklat kemasan di Kota Makassar. Pendekatan penelitian ini menggunakan penelitian survey yang mengambil sampel dari satu populasi dan menggunakan kuisioner sebagai alat pengumpul data yang pokok. Pelaksanaan penelitian dilakukan pada pengusaha UKM coklat kemasan di Kota Makassar. Waktu penelitian dilakukan mulai Desember 2015 sampai dengan Pebruari 2016. Populasi yang digunakan dalam penelitian ini adalah semua pengusaha UKM coklat kemasan di Kota Makassar berjumlah 20 orang. Pemilihan sampel dalam penelitian ini dilakukan dengan menggunakan metode sampling jenuh (sensus), dimana semua populasi dijadikan sampel, sebanyak 20 orang pengusaha UKM coklat kemasan Kota Makassar. Teknik analisa data kuantitatif yang diperoleh dari hasil kuesioner dengan menggunakan analisis regresi berganda (multiple regression analysis). Hasil penelitian ini menunjukkan bahwa strategi pembinaan Usaha Kecil Menengah Dinas Koperasi dan UKM kota Makassar cukup baik jika di lihat dari 3 aspek strategi yaitu cost leadership (Biaya Rendah termasuk biaya produksi , alat dan bahan baku) , differentiation (Menciptakan produk yang berbeda dan unik) , dan focus (Target pembeli , segmen produk dan Lokasi pemasaran). Hal ini dapat di lihat dari adanya Pengaruh Pelatihan, munculnya Motivasi yang kuat dan peningkatan Pengetahuan Kewirausahaan Terhadap Kinerja Pengusaha Kecil Menengah Coklat Kemasan di Kota Makassar